Penerapan Kitab Undang Hukum Pidana Dan Kitab Undang Hukum Acara Pidana Dalam Penyelesaian Perkara Pidana Pemilu - Dahri, Muhtar; Sayuti, Salman; Chandra, Febrian (Universitas Batanghari Jambi, 2023)
Simultaneous general elections held by the State of Indonesia to elect the President, Vice President, Members of Parliament, Governor and Regent caused various kinds of problems, one of which was in the form of criminal cases, which subsequently led to polemics in related agencies in terms of determining the forms and placing the articles of election criminal cases and their resolution, Therefore, this study attempts to examine the problem of normative research methods by the method of document overview on the application of the Wetboek Van Strafrecht in the specific provisions of the laws on electoral crimes in electoral laws and regulations and on the resolution of electoral criminal cases that refer to Wetboek Van Strafrecht unless the electoral law provides otherwise, that the application of the provisions on electoral criminal cases and their resolution requires a detailed understanding of the parties involved in the electoral process. Therefore, there is a need for training and guidance for stakeholders namely Gakkumdu, in relation to the Electoral Crimes Ordinance and its resolution procedures; To avoid causing disputes within competent authorities in determining the difference between electoral offenses and common offenses